The Influence of the Character-Oriented Rambu Solo’ Ceremony-Based Learning Model (Purso) on Improving Learning Outcomes in Civics Education - Allolinggi, Lutma Ranta; Maminiaina (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This study aims to investigate the effect of the Character-Oriented Rambu Solo’ Ceremony-Based Learning Model (PURSO) on students’ learning outcomes in Civics Education. The integration of local cultural values into character education is considered essential to fostering moral, social, and cognitive development among elementary school students. Method:This study adopts a quasi-experimental design using a